Efficient and Highly Air Stable Planar Inverted Perovskite Solar Cells with Reduced Graphene Oxide Doped PCBM Electron Transporting Layer. Issue 7 (14th December 2016) - Kakavelakis, George; Maksudov, Temur; Konios, Dimitrios; Paradisanos, Ioannis; Kioseoglou, George; Stratakis, Emmanuel; Kymakis, Emmanuel
Abstract : Reduced graphene oxide (rGO) is added in the [6, 6]‐Phenyl‐C61‐butyric acid methyl ester (PCBM) electron transport layer (ETL) of planar inverted perovskite solar cells (PSCs), resulting in a power conversion efficiency (PCE) improvement of ≈12%, with a hysteresis‐free PCE of 14.5%, compared to 12.9% for the pristine PCBM based device. The universality of the method is demonstrated in PSCs based on CH3 NH3 PbI3− x Cl x and CH3 NH3 PbI3 perovskites, deposited through one step and two step spin coating process, respectively. After a comprehensive spectroscopic characterization of both devices, it is clear that the introduction of rGO in PCBM ETL results in an important increase of the ETL conductivity, together with reduced series resistance and surface roughness. As a result, a significant photoluminescence quenching of such perovskite/ETL is observed, confirming the increased measured short circuit current density. Transient absorption measurements reveal that in the rGO‐based device, the relaxation process of the excited electrons is significantly faster compared to the reference, which implies that the charge injection rate is significantly faster for the first. Furthermore, the light soaking effect is significantly reduced. Finally, aging measurements reveal that the rGO stabilizes the ELT/perovskite interface, which results in the stabilization of perovskite crystal structure after prolonged illumination. Abstract : Planar inverted perovskite solar cells with high efficiency and ambient stability are fabricated based on a reduced graphene oxide (rGO) doped [6, 6]‐Phenyl‐C61‐butyric acid methyl ester (PCBM) electron transporting layer (ETL). The performance improvement is attributed to enhanced electron extraction, while the enhancement in the lifetime is due to the stabilization of the perovskite/ETL interface of the rGO doped device compared to the pristine.